Juridical Analysis of the Application of Bankruptcy Requirements in Commercial Court Practice in Indonesia - Yuli Sarwanto; Siciliya Mardian Yoel; Nur Chasanah (Journal of Law, Politic and Humanities, 2026)
This study sets out to analyze the practical implementation of bankruptcy requirements in Indonesia’s commercial courts, along with its impact on the legal safeguards available to both debtors and creditors. According to Indonesian law specifically Law Number 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations a bankruptcy petition requires at least two creditors and one payable debt that has matured. Adopting a normative juridical approach, the research draws on statutory and conceptual frameworks, and qualitatively examines primary, secondary, and tertiary legal sources. The results show that in commercial court practice, the enforcement of bankruptcy conditions tends to focus on formal criteria via the simple proof doctrine, often overlooking a comprehensive review of the debtor’s financial standing. This gives rise to several juridical issues, including the absence of an insolvency test, the potential misuse of bankruptcy as a pressure tool by creditors, and inconsistencies in court decisions interpreting “due and payable debt.” The implications reveal an imbalance in legal protection between debtors and creditors. Debtors are vulnerable to being declared bankrupt despite being solvent, while creditors may suffer losses due to premature proceedings. Therefore, optimization is needed through legal reformulation, strengthening jurisprudential guidelines, and enhancing the effectiveness of the Suspension of Debt Payment Obligations (PKPU) mechanism. In conclusion, the application of bankruptcy requirements in Indonesia still requires improvement to better reflect the principles of justice, legal certainty, and utility in a balanced manner.